Somalia : Request for an Extension of the Arrangement Under the Extended Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2022)
In the attached letter, the Somali authorities request an extension of the date on which the arrangement under the Extended Credit Facility (ECF) will automatically expire unless a review is completed to August 17, 2022. On March 25, 2020, the Executive Board approved Somalia's HIPC Initiative Decision Point1 and a three-year arrangement under the ECF.2 The first review under the ECF arrangement was completed by the Executive Board on November 18, 2020.3 However, as no review has been completed since then, the ECF arrangement is set to automatically expire on May 17, 2022, in line with the rule on automatic expiration of ECF arrangements if no review has been completed for 18 months. Under Fund policy, the Board may decide to delay the automatic expiry of the arrangement by up to three months if staff and the authorities appear close to reaching understandings on targets and measures to put the ECF-supported program back on track.